Depression and Anxiety as Risk Factors for Vitiligo - Lulu Setyawati Purwaningsih; Moh. Shoim Dasuki; Metana Puspitasari; Ratih Pramuningtyas (Lembaga Pengembangan Kinerja Dosen, 2025)
vitiligo is a disease characterized by the selective loss of melanocytes, resulting in non-scaly chalk-white macules. There is no hypothesis that can clearly explain the scientific cause of vitiligo. However, some studies have indicated that stress and emotional pressure factors, such as anxiety, may contribute to the development or exacerbation of this condition. Research Objective: this study aims to determine whether there is a relationship between depression and vitiligo, whether there is a relationship between anxiety and vitiligo, whether there is a relationship between smoking and vitiligo, and whether there is a relationship between depression and anxiety with vitiligo. Method: analytical observational research using a cross-sectional method is the research design employed. Purposive sampling is used to select the population based on inclusion and exclusion criteria, resulting in 53 responses. This study was conducted by interviewing patients using the Beck Depression Inventory and Beck Anxiety Inventory questionnaires, assisted by the researcher. Data analysis used univariate, bivariate, and multivariate analysis. Results: findings indicate that the significance value of Pearson chi-square is 0.001 < 0.05, meaning there is a significant relationship between depression and vitiligo. There is a significant relationship between anxiety and vitiligo with a significance value of Pearson chi-square 0.003 < 0.05. Simultaneously, depression and anxiety have a significant relationship with vitiligo. Conclusion: from the research results, it can be concluded that 30% of depression and anxiety can be the cause of vitiligo occurrences. Based on these conclusions, the suggestion that can be used as a consideration is that this research can be used as a basis for further research that links risk factors with the severity of vitiligo.